Cosmic Grace and Humble Prayer: The Ecological Vision of the Green Patriarch Bartholomew I - Arickappillil, Isaac (Journal of Dharma, 2003)
Cosmic Grace and Humble Prayer analyses the ecological vision of the Green Patriarch Bartholomew I. The work is edited and translated from the original Greek by John Chryssavgis with a foreword by Metropolitan John (Zizioulas) of Pergamon. There is a beautiful unity between the foreword, acknowledgements, long introduction and the text of the book. Metropolitan John of Pergamon points out that the present day ecological crisis is rooted in theology, and it is above all a spiritual problem. The church has to revise her pastoral teachings, and work as to transform the mentality and attitude of modern people, making them realize that the protection of the natural environment is a fundamental religious obligation demanded from humankind by God himself. Human being is the priest of creation who takes the world in his hands as a ‘gift’ and refers it back to God in thankfulness by sharing it with others in love which itself is a eucharistic action and a manifestation of an ascetic mentality enabling him to overcome his selfishness.